KARAKTERISTIK MANTAN BURUH MIGRAN INDONESIA PENERIMA DANA CSR PERBANKAN DI KECAMATAN DONOMULYO KABUPATEN MALANG - Latifah, Sri Wahjuni (Journal of Innovation in Business and Economics, 2013)
Research on the characteristics of Indonesian Migrant Workers Former grantees Banking CSR is done in District Donomulyo Malang. The purpose of this study is to provide empirical evidence about the characteristics of former migrant workers so as to be considered the government to improve their welfare. Quota sampling techniques obtained 45 respondents. Data analysis with quantitative and qualitative approaches. The results of this study indicate that migrant workers productive age (35.28 years) with an average experience of 5.8 years. The level of high school education. His favorite of Taiwan. Investment enough value the average Rp.108.000.000